STUDY OF THE CONNECTIONS BETWEEN HYPERINSULINEMIA AND GLUCOSE INTOLERANCE IN EARLY-ONSET CORONARY ARTERY DISEASE Dr. Gaurav Gohad - Gohad , Gaurav (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Indians experience their first myocardial infarction 5 to 10 times sooner than other populations, and they experience coronary artery disease (CAD) 5 to 10 years earlier than other populations. IGT, also known as type 2 diabetes, has several risk factors in common with coronary artery disease (CAD), and an increase in the prevalence of diabetes also suggests a rising risk of CAD.Aims & objectives: The current study looked at the relationships between early-onset coronary artery disease, glucose intolerance, and hyperinsulinemia in tertiary care hospital patients.Material and Methods: The current study involved subjects with coronary artery disease who were either male or female and under the age of 45. Serum insulin levels and glucose intolerance (GI) were assessed.Results: 42 patients in all who met the study requirements were included in the current study. The average age was 42.07 5.39. Males (73,81%) outnumbered females (26,19%). The average BMI was 23.26 3.33 kg/m2. The prevalence of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), diabetes mellitus (DM), and hyperinsulinemia (>25 IU/ml) were 9.52%, 7.14%, 7.14%, and 9.52%, respectively, in the current study. There were 14.29% cases of glucose intolerance overall (12 patients). Major risk factors identified in the current study included hypertension (26.19%), BMI (> 25 kg/m2) (26.19%), smoking (21.43%), dyslipidemia (19.05%), family history of CAD (16.67%), and family history of diabetes (14.29%). We found a statistically significant difference between patients with normoglycemia and those with glucose intolerance in their fasting plasma glucose (mg/dl), 2-hour plasma glucose (mg/dl), fasting serum insulin (uIU/ml), and HbA1C values.Conclusion: Early diagnosis through testing for glucose intolerance is strongly advised in high risk individuals because it is linked to early-onset coronary artery disease and hyperinsulinemia.Keywords: early-onset coronary artery disease, glucose intolerance, hyperinsulinemia, impaired glucose tolerance